Examining Reported Versus Actual Attendance in College Basketball Non-Conference Games: Do Scheduling Elements Make a Difference? - Nels Popp; Stephen Shapiro; Jason Simmons; Ryan Dastrup (Journal of Applied Sports Management, 2024)
This study examines factors impacting sport attendance at non-conference NCAA Division I men’s college basketball games. Non-conference college basketball games are relatively unique because athletic department personnel control many of the scheduling variables related to event popularity, including opponent, game day, and start time. As such, it is valuable for administrators to know which elements might maximize event revenue. The current study is also unique because it examines both reported attendance (tickets disseminated) and actual attendance (tickets scanned at the venue). A total of 48 schools provided ticket scan rate data for their non-conference home basketball games over three seasons (2017-2020), with a total of 964 observations. Results revealed a no-show rate of 37%. Several factors affecting reported attendance were significantly different than those affecting actual attendance, including weekend games, geographic distance between schools, and home team winning percentage. Results were also different between Power Five institutions and non-Power Five institutions.
Keywords: college basketball; attendance; demand; non-conference; scheduling